2016
DOI: 10.12989/scs.2016.20.3.571
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis and design of concrete-filled dual steel tubular columns under axial loading

Abstract: A new unified design formula for calculating the composite compressive strength of the axially loaded circular concrete filled double steel tubular (CFDST) short and slender columns is presented in this paper. The formula is obtained from the analytic solution by using the limit equilibrium theory, the cylinder theory and the "Unified theory" under axial compression. Furthermore, the stability factor of CFDST slender columns is derived on the basis of the Perry-Robertson formula. This paper also reports the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 20 publications
(31 reference statements)
0
43
0
Order By: Relevance
“…Little research has been reported on the structural behavior of thin-walled CFDST square columns that are subjected to eccentric loads. This paper Most of the investigations on CFDST columns reported previously has focused on circular cross-section [1][2][3][4][5][6][7][8][9][10][11][12] and tests on short square CFDST columns consisting of an inner circular steel tube have been very limited [13][14][15][16]. Pei [13] performed tests to determine the structural performance of stub CFDST square columns under axial and eccentric loads.…”
Section: Introductionmentioning
confidence: 99%
“…Little research has been reported on the structural behavior of thin-walled CFDST square columns that are subjected to eccentric loads. This paper Most of the investigations on CFDST columns reported previously has focused on circular cross-section [1][2][3][4][5][6][7][8][9][10][11][12] and tests on short square CFDST columns consisting of an inner circular steel tube have been very limited [13][14][15][16]. Pei [13] performed tests to determine the structural performance of stub CFDST square columns under axial and eccentric loads.…”
Section: Introductionmentioning
confidence: 99%
“…In comparisons with experimental studies on CFST columns, only limited experimental investigations on CFDST columns with circular sections were performed by researchers, such as Xiong et al [6], Peng et al [8], Liew and Xiong [9], Romero et al [10], Wan and Zha [11], Ekmekyapar and Al-Eliwi [12]and Ibañez et al [13]. Peng et al [8] Experimental observations indicated that the column ultimate strengths were reduced by increasing the / o o D t ratios of the outer tube.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies on circular CFDST short column constructed by carbon steel tubes have been extremely scare [11,27]. Wan and Zha [11] proposed a confining pressure model and a softening reduction factor as a function of confining factors for determining the post-peak responses of concrete in CFDST columns. However, it was found that the computed axial loadstrain curves deviated considerably from experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Computational and experimental investigations on the responses of circular short CFDST columns subjected to axial loading have been undertaken by researchers, such as Peng et al [9], Hassanein et al [10], Wan and Zha [11], Xiong et al [12], and Ekmekyapar and Al-Eliwi [13].…”
Section: Introductionmentioning
confidence: 99%